Substantiating the requirements to functional indicators for the manipulators of mobile robotic demining complexes - Strutynsky, Vasil; Kotsiuruba, Volodymyr; Dovhopoliy, Anatoliy; Husliakov, Oleh; Budianu, Radu; Kolos, Oleksii; Hrechka, Iryna (Eastern-European Journal of Enterprise Technologies, 2019)
It has been proposed that humanitarian demining should involve mobile robotic complexes equipped with manipulators based on mechanisms with parallel kinematic structures. The features of design and characteristics of the manipulators have been considered. We have established special features in equipping the manipulators, used to directly manipulate objects. The geometrical and strength parameters for the threaded connection between a fuse and a mine shell have been determined. A scheme of efforts interaction in the threaded connection has been substantiated. We have found patterns in the emergence of the thread force reactions under a gravitational load of the fuse and at thread tightening. The efforts that arise at unscrewing the fuse of an anti-tank mine by the manipulator have been experimentally determined. The measurements employed specialized equipment in the form of a set of special grips. The result of measurements is the established effort of thread tightening and the momentum loads required for unscrewing the fuse. We have substantiated the rational kinematic and dynamic algorithms of the manipulator operation in the process of unscrewing the fuse. To this end, we measured the displacements of the fuse under the action of asymmetrical force and momentum loads. The measurements of parameters have been performed of cyclic loads necessary to unfix the threaded connection between the fuse and a mine. A special algorithm of dynamical loads on the fuse has been suggested, which ensures rational conditions for its unscrewing. The paper reports results from experimental study into remotely-controlled disposal of explosive objects and unexploded ammunition using an example of an anti-tank mine. We have shown feasibility of the proposed technology of humanitarian demining of territories containing explosive objects.